Resveratrol Attenuates Rheumatoid Arthritis Induce Neutrophil Extracellular Traps via TLR-4 Mediated Inflammation in C57BL/6 Mice - Chen, Z; Xiao, G; Ao, J (Physiological research, 2024)
The objective of this study was to evaluate whether RSV inhibits neutrophil extracellular traps (NETs) that induce joint hyperalgesia in C57BL/6 mice after adjuvant-induced arthritis. A subplantar injection of Freund's complete adjuvant was administered to C57BL/6 mice on day 0 for immunization in the AIA model. Resveratrol (RSV, 25 mg/kg) was administered intraperitoneally once daily starting on day 22 and continuing for two weeks. The effects of mechanical hyperalgesia and edema formation have been assessed in addition to histopathological scoring. Mice were sacrificed on day 35 to determine cytokine levels and PADI4 and COX-2 expression levels. ELISA was used to quantify neutrophil extracellular traps (NETs) along with neutrophil elastase-DNA and myeloperoxidase-DNA complexes in neutrophils. An immunohistochemical stain was performed on knee joints to determine the presence of nuclear factor kappa B p65 (NF-kappaB p65). AIA mice were found to have higher levels of NET in joints and their joint cells demonstrated an increased expression of the PADI4 gene. Treatment with RSV in AIA mice (25 mg/kg, i.p.) significantly (P<0.05) inhibited joint hyperalgesia, resulting in a significant increase in mechanical threshold, a decrease in articular edema, a decrease in the production of inflammatory cytokines, increased COX-2 expression, and a decrease in the immunostaining of NF-kappaB. Furthermore, treatment with RSV significantly reduced the amount of neutrophil elastase (NE)-DNA and MPO-DNA complexes, which were used as indicators of NET formation (P<0.05). This study indicates that RSV reduces NET production and hyperalgesia by reducing inflammation mediated by PADI4 and COX-2. According to these data, NETs contribute to joint pain and resveratrol can be used to treat pain in RA through this pathway.
Keywords: Animals; extracelulární pasti; zánět; Hyperalgesia; Arthritis, Rheumatoid; Cytokines; revmatoidní artritida; Leukocyte Elastase; Cyclooxygenase 2; Resveratrol; toll-like receptor 4; edém; cytokiny; DNA; Mice; myši; resveratrol; Inflammation; hyperalgezie; Extracellular Traps; cyklooxygenasa 2; Neutrophils; leukocytární elastasa; Toll-Like Receptor 4; neutrofily; NF-kappa B; zvířata; Mice, Inbred C57BL; Edema; myši inbrední C57BL